Stratigraphic architecture of the Bonifacio Basin (South Corsica, Early-Middle Miocene) - M. Brandano; L. Tomassetti; F. Jadoul; F. Berra; A. Lanfranchi; M.R. Petrizzo (null, 2008)
This study analyse the geometrical and spatial relationship of the lithostratigraphic units of the Bonifacio basin. The Miocene sediments of are divided by Ferrandini et al (2003) in two formations: the Cala di Labra Formation and the Bonifacio Formation. The Miocene transgression in the Bonifacio Basin is attributed to the early Burdigalian (Galloni et al., 2001; Ferrandini et al., 2003). Our preliminary data from the planktonic foraminifera assemblages suggest that the Bonifacio F. is late Burdigalian (Globigerinoides trilobus, G. altiaperturus, G. predehiscens) and only the upper part could be assigned to the uppermost Burdigalian\lower Langhian (Globoquadrina dehiscens, Globigerinelloides bisfericus) stratigraphic interval. In the eastern part of the Bonifacio Basin (Cala di Labra) the initial portion of the succession belongs to the Cala di Labra F. It consists of up to 5 meters of a coral-rich interval directly lying on the Variscan granitic basement. Coral colonies are associated to bioclastic packstones made up mainly by large benthic foraminifera, porcellaneous foraminifera and red algae debris. The coral unit is overlain by about 15 m of fining upward prevailing quartzose to bioclastic sandstone associated with fine-grained conglomerates close to the base. This deposit passes upward to 10 m of hybrid calcarenites and grey silty marls. A well evident discontinuity surface marks the passage to the Bonifacio F. Here large scale clinoforms, prograding to SW characterize this formation represented by hybrid bioclastic grainstones to rudstones. Moving to the central part of the Bonifacio Basin (from Capo Pertusato to Bonifacio) only the Bonifacio Formation outcrops. In the Bonifacio section the basal lithozone consists of 15 m-thick cross-bedded hybrid sandstones. The skeletal fraction is dominated by large benthic foraminifera, small benthic foraminifera and by other skeletal grains (bryozoans, balanids, echinoid and molluscs). Extraclasts are quartz, feldspar and granitic rock fragments. This level is ...